Spatial variation of strong ground motions in a heterogeneous soil site based on observation records from a dense array - Yang, Qianli; Yu, Ruifang; Jiang, Peng; Chen, Kexu (Frontiers in Earth Science, 2023)
The difference of local sediment thickness and soil properties have a significant impact on the spatial variation mechanism of seismic ground motion in engineering scale. Due to the scarcity of observation data of dense array, the existing theoretical studies are mostly developed by numerical simulation methods , including human factors and a large number of assumptions. In view of this, based on the multi-station observation records of Luxian Ms6.0 earthquake and Yibin Ms5.1 earthquake obtained by Zigong dense array, the paper quantitatively analyzes the spatial characteristic of ground motion in heterogeneous soil sites by integrating theoretical model with numerical analysis. In this study, many popular approaches including root-mean-square acceleration , Horizontal-to-Vertical spectral ratio (HVSR) of microtremor and strong motion records, and lagged coherency are comprehensively utilized to make the conclusion accurate and reliable. The results show that local soil conditions could affect the attenuation of coherence function with distance. The station-pairs with similar HVSR characteristics generally present higher coherence level when the difference of inter-station distance is less than 100 meters. In addition, the coherency function between stations will be greatly reduced when the H/V spectral ratio characteristics differ greatly, which is also obvious in the low-frequency part below 5Hz. Finally, a lagged coherency model which considers the influence of heterogeneous soil is constructed in this paper. The model has definite physical meaning and can better represent the spatial variation of ground motion at non-bedrock sites.